Tack behaviour of unvulcanized and vulcanized natural rubber latex films / Asiah Abdullah and Azemi Samsuri - Abdullah, Asiah; Samsuri, Azemi (Institute of Research, Development and Commercialization, Universiti Teknologi MARA, 2005)
Sealing property of rubbers is directly related to tack. The present work investigates the effect of crosslink concentration, leaching and types of crosslink on tack strength of natural rubber (NR) latex films. The tack strength of dry rubber vulcanizates and latex vulcanizates are also compared. The results show that introduction of crosslinks reduced the tack strength, leaching increased tack strength; maturation and types of crosslink do not affect the tack strength. The tack behaviour of dry rubber and leached latex vulcanizates is comparable.